2022
DOI: 10.1007/s00705-022-05453-3
|View full text |Cite
|
Sign up to set email alerts
|

An updated review and current challenges of Guanarito virus infection, Venezuelan hemorrhagic fever

Abstract: Guanarito virus (GTOV) is a member of the family Arenaviridae and has been designated a category A bioterrorism agent by the US Centers for Disease Control and Prevention. It is endemic to Venezuela’s western region, and it is the etiological agent of “Venezuelan hemorrhagic fever” (VHF). Similar to other arenaviral hemorrhagic fevers, VHF is characterized by fever, mild hemorrhagic signs, nonspecific symptoms, thrombocytopenia, and leukopenia. Patients with severe disease usually develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
0
11
0
2
Order By: Relevance
“…Seropositivity and virus isolation from VHF’s primary rodent reservoir host, Zygodontomys brevicauda (Short-tailed Cane Mouse), points to an endemic area of 9,000 km 2 located in the southern and southwestern areas of Venezuela (Fig. 1 ; [ 33 ]). Both GTOV in rodents and human cases of VHF have been reported in the states of Portuguesa and Barinas [ 33 ].…”
Section: Endemicity and Reservoirsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seropositivity and virus isolation from VHF’s primary rodent reservoir host, Zygodontomys brevicauda (Short-tailed Cane Mouse), points to an endemic area of 9,000 km 2 located in the southern and southwestern areas of Venezuela (Fig. 1 ; [ 33 ]). Both GTOV in rodents and human cases of VHF have been reported in the states of Portuguesa and Barinas [ 33 ].…”
Section: Endemicity and Reservoirsmentioning
confidence: 99%
“…1 ; [ 33 ]). Both GTOV in rodents and human cases of VHF have been reported in the states of Portuguesa and Barinas [ 33 ]. Isolates of GTOV have also been found in Oligoryzomys delicatus (Delicate Pygmy Rice Rat) and Sigmodon alstoni (Groove-toothed Cotton Rat) within these states [ 34 ].…”
Section: Endemicity and Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vaccine platforms and strategies outlined in this review will mainly focus on LF and AHF. Incidents of other mammarenavirus infections are rare compared to LF and AHF, although the development of vaccines against them remains crucial, as cases of VHF, BzHF, and CHF were reported recently [ 20 , 48 , 49 ]. Various vaccine platforms have been investigated, ranging from live-attenuated vaccines, artificially modified recombinant viruses, the use of other viruses as vectors, as well as proteins, DNA, and mRNA [ 3 , 4 , 5 , 7 , 11 ].…”
Section: Arenavirus Vaccine Developmentmentioning
confidence: 99%
“…Caffeine may decrease endotoxins' lipopolysaccharide (LPS)‐induced inflammatory reactions according to in vitro findings (Hwang et al, 2016). A recent human investigation in obese females found that caffeine suppressed LPS (Silva‐Ramos et al, 2022). The study also discovered that caffeine reduces obesity‐related metabolic side effects such as increased LPS, insulin action, glucose homeostasis, and testosterone levels after a high‐intensity exercise lifestyle intervention.…”
Section: Food That Decreases Virus Loadmentioning
confidence: 99%